Study on the effect of human resource management practices on employee retention in Syarikat Air Melaka Berhad (SAMB) / Nurul Syazwanie Hasrul ‘Azam and Zuliyana Esan - Hasrul ‘Azam, Nurul Syazwanie; Esan, Zuliyana (Faculty of Business and Management, 2016)
The purpose of the study is to investigate the effect of human resource management practices on employee retention in Syarikat Air Melaka Berhad (SAMB). Human resource management practices which consists of selection, training and development, career planning and compensation become the independent variables meanwhile employee retention become the dependent variable in this study. The research carried out with sample size of minimum 152 workers from the total population of 242 workers of SAMB. Moreover, the data collected by using a detailed structured questionnaire that need to be answer by respondents. In addition, the researchers also used Simple Random Sampling (SRS) method in order to gain the data from respondents. Thus, the result of findings showed there was a significant and positive relationship between human resource management practices and employee retention.